2004
DOI: 10.1074/jbc.m306814200
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Short, Strong Hydrogen Bond in the Active Site of Hydroxynitrile Lyase from Hevea brasiliensis Explains a Large pK Shift of the Catalytic Base Induced by the Reaction Intermediate

Abstract: The calculations explain all the NMR features, i.e. they suggest why a short, strong hydrogen bond is formed upon inhibitor binding and why this short, strong hydrogen bond reverts back to a normal one at ϳpH 8. Importantly, the computations also yield a shift of the free energy of the anionic state relative to the zwitterionic reference state by about 10.6 kcal/mol, equivalent to a shift in the apparent pK a of His 235 from 2.5 to 10. This huge inhibitor-induced increase in basicity is a prerequisite for His … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 57 publications
3
46
0
Order By: Relevance
“…Such a strong, short hydrogen bond has previously been both calculated (15) and experimentally monitored (29). In our models, it is formed only in those settings from which cyanohydrine is synthesized (QC2 and QC5 in Table 6), confirming its crucial role.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Such a strong, short hydrogen bond has previously been both calculated (15) and experimentally monitored (29). In our models, it is formed only in those settings from which cyanohydrine is synthesized (QC2 and QC5 in Table 6), confirming its crucial role.…”
Section: Discussionsupporting
confidence: 52%
“…This means that upon binding of the cyanide compound, His 235 would turn into a powerful agent for the deprotonation of HCN. The pK a of His 235 is ϳ4 in the free enzyme (15,28,29), and indeed this residue appears deprotonated in the NAT structure. This indicates that the incoming ligand(s) severely affect the pK a of the catalytic residues and, together with the apparent high mobility of the protons in the active site observed from the QC results, supports the idea that the reaction mechanism functions via a protonation-deprotonation sequence (15).…”
Section: Discussionmentioning
confidence: 99%
“…When these enzymes interact with their mechanism-based inhibitors, the imidazole ring in the side chain of the central histidine is protonated, and its hydrogen bond with the acidic residue is greatly strengthened, leading to a significant downfield shift of the corresponding proton signal into the 16 -19.5-ppm range (45)(46)(47). Based on these facts, we used NMR spectroscopy to detect the proton in the strong hydrogen bond between the side chains of Asp 201 and His 232 in the catalytic triad of 15 N-labeled MenH.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxynitrile lyase:thiocyanate complex: Stranzl et al 74 have shown by NMR spectroscopy that the pK a value of His235 in hydroxynitrile lyase increases from 2.5 to $8 upon binding of thiocyanate. The current version of PROPKA 2.0 does not treat S atoms as an ionizable group.…”
Section: Charged Ligandsmentioning
confidence: 99%